2020
DOI: 10.1161/atvbaha.119.313046
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular Effects of Androgen Deprivation Therapy in Prostate Cancer: Contemporary Meta-Analyses

Abstract: Androgen deprivation therapy is a cornerstone of prostate cancer treatment. Pharmacological androgen deprivation includes gonadotropin-releasing hormone agonism and antagonism, androgen receptor inhibition, and CYP17 (cytochrome P450 17A1) inhibition. Studies in the past decade have raised concerns about the potential for androgen deprivation therapy to increase the risk of adverse cardiovascular events such as myocardial infarction, stroke, and cardiovascular mortality, possibly by exacerbating cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
124
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(128 citation statements)
references
References 69 publications
0
124
2
2
Order By: Relevance
“…Despite publications on multiple studies and meta-analyses, the effect of ADT on patients was still controversial. In general, meta-analysis of observational studies supported a positive relationship between increased cardiovascular risk and ADT, while the results from randomized studies were negative 9 . Hu et al proposed that the reason for the conflicting outcomes might be related to the study designs 9 .…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…Despite publications on multiple studies and meta-analyses, the effect of ADT on patients was still controversial. In general, meta-analysis of observational studies supported a positive relationship between increased cardiovascular risk and ADT, while the results from randomized studies were negative 9 . Hu et al proposed that the reason for the conflicting outcomes might be related to the study designs 9 .…”
Section: Discussionmentioning
confidence: 92%
“…While most of the observational studies on Caucasian population indicated that ADT would increase the cardiovascular risk of patients 9,22 , the results for Asians suggested otherwise. In several observational studies based on national insurance databases in different populations, the results did not show an increased cardiovascular risk in Asian patients receiving ADT [13][14][15] .…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, compared to the surgery-only group, the ADT group had markedly greater risk of IHD and stroke. While many studies have shown that ADT is associated with CVD [5][6][7][8][9][10][11][12][13][14] , other studies [15][16][17] have demonstrated conflicting results, which were attributed to differences in the prior history of CV events or type and duration of ADT. A meta-analysis using randomized controlled trials (RCTs) suggested no increased risk of fatal CVD associated with ADT 17 , but pooled analyses of observational studies showed consistent evidence of increased risk of CVD, regardless of the type of ADT therapy 6 .…”
Section: Discussionmentioning
confidence: 99%
“…Low serum testosterone levels are associated with increased atherosclerosis and risk of cardiovascular mortality, both in men with spontaneous age-associated serum testosterone decline [1], and in patients receiving androgen deprivation therapy (ADT) to control prostate cancer [2]. Meta-analysis of randomized clinical trials of ADT, on the other hand, has failed to replicate the finding from observational studies and causality of the association between castration and cardiovascular disease thus remains unresolved [3].…”
Section: Introductionmentioning
confidence: 99%